Clinical Outcomes of Lichtenstein Repair for Adult Inguinal Hernia: A Decade of Experience in a Tertiary Care Hospital of Bangladesh - Saha, Krishna Pada; Mohammad Asadur Rahman; Md Fazlul Karim Chowdhury; Abullah Al Shah Newaz; Md Shahidul Islam; Muhammad Ali Siddiquee; Most Bilkis Fatema; Abu Saleh Ahmed; Alam, S M Syeed Ul; Debashish Nasker (Bangladesh Medical Journal, 2026)
The introduction of tension-free mesh repair, particularly the Lichtenstein technique, has markedly improved surgical outcomes by reducing recurrence rates and postoperative morbidity. Despite its widespread adoption, evaluation of clinical outcomes and complication profiles remains essential, especially in resource-limited settings. To assess the feasibility, safety, and clinical outcomes of open tension-free mesh repair using the Lichtenstein technique in adult patients with inguinal hernia, this prospective observational study was conducted at Shaheed Suhrawardy Medical College Hospital, Dhaka, Bangladesh, over ten years from January 2009 to December 2018. A total of 897 adult patients with primary inguinal hernia underwent open Lichtenstein tension-free mesh repair using polypropylene mesh. Patients with recurrent, obstructed, or strangulated hernias and those unfit for surgery were excluded. The evaluation before surgery involved a clinical assessment and routine investigations. Surgeries were performed under spinal or local anaesthesia following a standardized technique. The main outcome measures included early postoperative complications like seroma, hematoma, wound infections, and testicular swelling, as well as late issues such as chronic groin pain and recurrence. Patients were evaluated at 6 weeks and 6 months post-surgery, with additional follow-up performed as needed. The data were analyzed using Microsoft Excel. Descriptive statistics were expressed as frequencies and percentages. Results were presented using tables and graphs where appropriate. Results: Among the 897 patients maximum (87.6%) of them were male, and male to female ratio was about 7:1, with a avarage age of 47 years, and the age range was 18 to 85 years. Indirect inguinal hernia was the most common type, observed in 63.2% patients, followed by direct hernia in 35.1% and pantaloon hernia in 1.7% cases. The majority (53.1%) of hernias were on the right side, while over one-third (38.1%) were found on the left side, and bilateral hernias constituted 8.8%. The average duration of the surgical procedure was 75.4 minutes, with a variation between 39 and 138 minutes, and there was no perioperative mortality. Early postoperative complications were infrequent. Seroma was noted in 1.78% patients, haematoma in 3.68%, testicular swelling in 5.24%, and wound infection in 0.78% patients. All complications were treated conservatively, and none necessitated the removal of the mesh. During the follow-up, late issues such as chronic groin pain (neuralgia) were reported in 4.35% patients, and hernia recurrence was found in 0.78% patients. There were no identified cases of mesh rejection or chronic discharging sinus. Open tension-free mesh repair using the Lichtenstein technique is a safe, effective, and reliable method for the management of primary inguinal hernia. It is related with low rates of postoperative complications, minimal chronic pain, and a very low recurrence rate. Given its simplicity and cost-effectiveness, this technique remains highly appropriate for routine use. Bangladesh Med J. 2025 May; 54(2) : 1-6